2011
DOI: 10.1186/1471-2261-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of caveolin in attenuation of cardioprotective effect of ischemic preconditioning in diabetic rat heart

Abstract: BackgroundNitric oxide (NO) has been noted to produce ischemic preconditioning (IPC)-mediated cardioprotection. Caveolin is a negative regulator of NO, which inhibits endothelial nitric oxide synthase (eNOS) by making caveolin-eNOS complex. The expression of caveolin is increased during diabetes mellitus (DM). The present study was designed to investigate the involvement of caveolin in attenuation of the cardioprotective effect of IPC during DM in rat.MethodsExperimental DM was induced by single dose of strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 65 publications
(72 reference statements)
4
40
0
Order By: Relevance
“…Hotta et al (2010) showed that the angiotensin II subtype 1 receptormediated upregulation of calcineurin in the diabetic rat heart interfered with the phosphorylation of Janusactivated kinase 2 and PI3K-Akt signaling, thereby affecting the efficacy of pharmacologic preconditioning. Ajmani et al (2011) provided data implicating caveolin, which was increased in the diabetic heart and interfered with endothelial NO synthase (eNOS) activity, contributing to the inability of the diabetic heart to respond to ischemic preconditioning. Impaired mitochondrial biogenesis, secondary to a dysfunctional adiponectinadenosine monophosphate-activated kinase (AMPK) axis , and increased TNFa-induced oxidative stress (Su et al, 2013) were also proposed as mechanisms underlying the greater sensitivity of the diabetic heart to ischemia/reperfusion injury and its resistance to ischemic preconditioning.…”
Section: Diabetesmentioning
confidence: 99%
“…Hotta et al (2010) showed that the angiotensin II subtype 1 receptormediated upregulation of calcineurin in the diabetic rat heart interfered with the phosphorylation of Janusactivated kinase 2 and PI3K-Akt signaling, thereby affecting the efficacy of pharmacologic preconditioning. Ajmani et al (2011) provided data implicating caveolin, which was increased in the diabetic heart and interfered with endothelial NO synthase (eNOS) activity, contributing to the inability of the diabetic heart to respond to ischemic preconditioning. Impaired mitochondrial biogenesis, secondary to a dysfunctional adiponectinadenosine monophosphate-activated kinase (AMPK) axis , and increased TNFa-induced oxidative stress (Su et al, 2013) were also proposed as mechanisms underlying the greater sensitivity of the diabetic heart to ischemia/reperfusion injury and its resistance to ischemic preconditioning.…”
Section: Diabetesmentioning
confidence: 99%
“…Current document is Daidzein restores the attenuated cardioprotective effect of IPC in ovariectomized rat heart, which may additionally be due to downregulation of caveolin that leads to elevated availability of NO and consequent increase in the activation of mitochondrial K ATP channels. The result show that perfusion of L-NAME, an eNOS inhibitor, and glibenclamide, a K ATP channel blocker, significantly attenuated the DDZ-induced cardioprotective impact of IPC in ovariectomized [83] and diabetic rat heart [13]. Gupta et al mentioned that activation of Heme oxygenase-1 via a specific activator, that is, hemin, restored the attenuated cardioprotective effect of IPC in diabetic rat heart by means of disrupting the caveolin-eNOS complicated and thereby enhancing the release of NO.…”
Section: Connection Of Ischaemic Preconditioning Through the Activitymentioning
confidence: 87%
“…Caveolin is the caveolar membrane protein which invaginated on the plasma layer that fills in as signaling stage for a considerable lot of G-protein coupled receptors [13]. Caveolin-1 gives off an impression of being embedded co-translationally into the ER membrane along its C-and N-terminal segments in the cytoplasm.…”
Section: Localization Of Caveolinmentioning
confidence: 99%
“…Potential roles for caveolin‐3 in T1D‐dependent diastolic dysfunction (Lei et al ., ), and impaired GLUT4 translocation (Penumathsa et al ., ) have been revealed in these rat studies. In terms of cardioprotection, one study indirectly implicates a role for elevated caveolin‐1 expression (Ajmani et al ., ), although caveolin levels were not measured and failure of preconditioning not confirmed (with omission of non‐preconditioned diabetic comparators). On the other hand, Li et al .…”
Section: Sarcolemmal Makeup and Cardioprotective Signallingmentioning
confidence: 99%